2012
DOI: 10.1029/2011ja017378
|View full text |Cite
|
Sign up to set email alerts
|

The relation between subauroral polarization streams, westward ion fluxes, and zonal wind: Seasonal and hemispheric variations

Abstract: The relation between subauroral polarization streams, westward ion fluxes, and zonal wind: Seasonal and hemispheric variations [1] We investigate the seasonal variation of the relation between SAPS (subauroral polarization streams) peak ion velocity and zonal wind velocity with coordinated DMSP and CHAMP satellite observations in both hemispheres, separately for Kp < 4 and Kp ≥ 4 geomagnetic conditions. Both SAPS and westward zonal wind peak almost at the same latitude. However, SAPS and zonal wind peak veloci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
41
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 58 publications
(72 reference statements)
7
41
0
Order By: Relevance
“…The elevated neutral temperature will increase the pressure gradient at high latitudes and further produces an enhanced equatorward meridional wind, which turns westward at middle and low latitudes under the Coriolis force. Observational evidence for that has also been provided by Wang et al []. They confirmed that both SAPS and westward zonal wind peak at almost the same latitude.…”
Section: Discussionsupporting
confidence: 72%
“…The elevated neutral temperature will increase the pressure gradient at high latitudes and further produces an enhanced equatorward meridional wind, which turns westward at middle and low latitudes under the Coriolis force. Observational evidence for that has also been provided by Wang et al []. They confirmed that both SAPS and westward zonal wind peak at almost the same latitude.…”
Section: Discussionsupporting
confidence: 72%
“…But the plasma velocity is much higher than that of the wind (e.g. Wang et al, 2012). Ion friction may thus be a relevant heating source.…”
Section: Zonal Wind Dependence On Imf B Y Signmentioning
confidence: 99%
“…During quiet times, zonal winds at middle and low latitudes are generally directed eastward from afternoon to early morning and westward for the other local times. The westward disturbance wind, which is partly related to the subauroral polarization streams (SAPS), is strongly enhanced from the afternoon to midnight sector, increasing with magnetic activity level (Wang et al, ). It is worthwhile to note that the CHAMP data in the paper of Xiong et al () do not represent winds well in the polar cap region.…”
Section: Introductionmentioning
confidence: 99%
“…The thermospheric convection response to ionospheric current systems was earlier investigated (e.g., Emmert et al, ; Förster et al, ; Lühr et al, ; Wang et al, ). The thermospheric vorticity was found to be closely related to the corresponding field‐aligned current (FAC) pattern (Förster et al, ).…”
Section: Introductionmentioning
confidence: 99%